Etiche in campo e responsabilità: La costruzione di un’etnografia sull’omogenitorialità tra Italia e California - Guerzoni, Corinna Sabrina (Antropologia Pubblica, 2024)
In this paper, I will reflect about the collection, the treatment and the restitution of data collected during my fieldwork between Italy and California. I briefly analyze the relation between ethics and anthropology, tracing some specific periods of the last decades that have played a peculiar role for the discipline. Then, I will focus around the concept of responsibility for the anthropologists on the fieldwork and beyond the fieldwork, showing how I have constructed my work with the informants involved in my ethnographic study.